From Newsroom Frames to Courtroom Registers: Language as Patriarchal Legitimation in Sexual Violence Reporting - Zulfiana Amaliana MZ; Aceng Ruhendi Saifullah; Yanty Wirza (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2025)
This study examines how patriarchal authority is linguistically constructed and contested across media coverage and courtroom registers in sexual violence cases. Using Critical Discourse Analysis (CDA) and Halliday’s transitivity framework, the researcher analyses 784 clauses from 25 online news articles and one courtroom case adjudicated at the Praya District Court in West Nusa Tenggara, Indonesia. News reports were selected through purposive sampling, focusing on cases where perpetrators were socially significant figures such as father, lecture, and religious leader. AntConc software generated frequency and concordance lists, which were qualitatively coded in ATLAS.ti to identity patterns of agency, responsibility, and identity representation. Findings reveal that media discourse is dominated by material processes (70%), foregrounding acts of abuse and institutional responses, while relational processes assign social roles that frame cases within patriarchal and hierarchies. Courtroom discourse is characterized by relational, verbal, and mental processes, where defendant deploy relational clauses and conditional threats to normalize coercion, mask abuse as paternal care, and silence resistance. This study introduces the concept of discursive paternalism to explain how paternal identity functions as a linguistic resource that reframes coercion as moral duty. By connecting media framing and courtroom registers, the analysis demonstrates that justice is discursively produced across interconnected arena, with media narratives priming societal expectations and courtroom language either reinforcing or challenging them